IMPLEMENTASI KAJIAN KITAB ADAB AL ‘ALIM WAL MUTA’ALLIM DALAM MENINGKATKAN ETIKA DAN PROFESIONALISME GURU - Asep Abduloh; Ahmad Sukandar; Marwan Setiawan (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study was to find out how the implementation of the study of the book of Adab al 'Alim wal Muta'allim in improving the ethics and professionalism of teachers at the Al Fauzaniyyah educational foundation. This research is a qualitative research with a descriptive method that focuses on planning, implementation, assessment as well as supporting and inhibiting factors of the study. data collection techniques through interviews, observations, documentation studies and literature studies. The results of the study focused on planning carried out by deliberation in choosing the book, the background for choosing the book, the time of the study, the selection of sources, to determining the achievement goals. The implementation of the study began with socialization to teachers and its implementation using the monologue and dialogue method. The assessment of the book study focuses on the participation of study participants, the study method, the time of the study, the contents of the book and the achievement of success. Supporting factors in the form of high enthusiasm, many teachers graduated from Islamic boarding schools, competent resource persons and a supportive environment. The inhibiting factors include the exclusion of some teachers, time inconsistency, lack of firmness of the foundation, the covid 19 pandemic. The conclusion of the study shows that the study of the book of Adab al 'Alim wal Muta'allim can improve the ethics and professionalism of teachers at the Al Fauzaniyyah Foundatio